Principle of transparency in procurement proceedings versus protection of the right to privacy (Ius Novum, 2019)
Transparency of public procurement proceedings is to safeguard the compliance with the principles of equal treatment, fair competition and proportionality, and eliminate the risk of arbitrariness of a buyer’s decisions. However, it is necessary to determine whether transparency covering the obligation to disclose information about people listed in contractors’ offers is not in conflict with the right to privacy, which is guaranteed by Article 7 of the Constitution of the Republic of Poland. The principle of transparency cannot lead to the infringement of another interest protected by the constitutional provision. It must also be implemented in accordance with the provisions of Regulation (EU) 2016/697. This means that personal data processed (made available) in public procurement proceedings must be protected. While disclosing the data concerning their qualifications, functions and no criminal record does not infringe the rights and freedoms of data subjects, the provision of information about conviction and a penalty adjudicated without a court’s ruling concerning making this information public would constitute a non-judicial sanction. The principle of transparency cannot result in sanctions that are not laid down in a sentence. It also cannot lead to discouraging persons from taking part in public procurement proceedings and, as a result, limiting competition. Therefore, it is necessary to protect information concerning the fact of conviction and a penalty imposed on persons whose data are listed in public procurement offers. At the same time, the data must be available to competitors of a contractor who provides the data of those people in an offer so that they can verify whether those persons’ conviction should or should not constitute grounds for excluding from a tender process and protect their right to receive an order. However, the legislator has not provided a safeguard so that, after the disclosure to competitors, the data will not be available to a wide circle of people and used for the purpose that is in conflict with statute.
Keywords: public procurement; transparency; right to privacy; personal data; no criminal record/no conviction